Implicações do pacto nacional de alfabetização na idade certa (PNAIC) - SILVA, Danila Castilho da (2019)
The present work deals with the implications of the National Pact of Literacy in the Right Age, the research is linked to the factors that approach educational policies of literacy, which is specifically the National Pact of Literacy in the Right Age (PNAIC). I tried to understand the impact of the program in the process of literacy and literacy, taking into account its methodologies and linguistic techniques, as well as its effectiveness. Based on this assumption, my intention was to address the literacy process within the program, to analyze if the objectives proposed by it are being successfully achieved, as well as to understand its challenges, limitations and failures. Based on this perspective, I will analyze the literacy concepts described by several authors, mainly Magda Soares (2004) and Emília Ferreiro (2015), as well as describe how the PNAIC has been implemented in schools in general. The methodological approach used to carry out the research was qualitative, being the data collection performed through semi-structured interviews and questionnaires.